Effect of Turmeric Powder Supplementation on Egg Production, Hatchability and Internal Egg Quality Characteristics of Quail Eggs - , S. D. Longjam; , R. Goswami; , G. Kalita; , A. K. Samanta; , F. A. Ahmed (Archives of Current Research International, 2024)
The present study was conducted to investigate the effect of different levels of dietary supplementation of turmeric powder at a rate 0, 1, and 2% on egg production, hatchability and internal egg quality characteristics of Japanese quails (Coturnix Japonica). A total of 225 numbers of 54 weeks old Japanese quails were randomly selected from the Poultry farm, Instructional Livestock Farm Complex, College of Veterinary Sciences and Animal Husbandry, Central Agricultural University, Selesih, Aizawl, Mizoram, of which 150 were female and 75 were male. The birds were divided equally into three treatment groups i.e. T0, T1 and T2 comprise of 75 birds each. T0, T1 and T2 were supplemented with 0, 1 and 2 per cent turmeric powder of basal diet respectively. Each group were again divided equally into five replicates trails. The mean Hen Day Egg Production (%) was significantly higher (P˂0.01) during 59th weeks of age in turmeric supplemented groups of T1 followed by T2. No significant difference was observed between the treatment groups in regard to hatchability percentage. Albumen index and Haugh unit were recorded as non- significant between the treatment groups. Yolk index and shell thickness was significantly higher at (P˂0.01) and (P˂0.05) respectively in 2 percent turmeric supplementation. The yolk colour score was found to be significantly higher (P˂0.01) with increased level of turmeric powder supplementation. Therefore, it is concluded that supplementation of 1% turmeric powder in the diet improve egg production while 2% inclusion improves the internal egg quality characteristics (yolk index and yolk colour) of quail eggs.